Analysis of necroptotic proteins in failing human hearts - Adrián Szobi; Eva Gonçalvesová; Zoltán V. Varga; Przemyslaw Leszek; Mariusz Kuśmierczyk; Michal Hulman; Ján Kyselovič; Péter Ferdinandy; Adriana Adameová (Journal of Translational Medicine, 2017)
Abstract Background Cell loss and subsequent deterioration of contractile function are hallmarks of chronic heart failure (HF). While apoptosis has been investigated as a participant in the progression of HF, it is unlikely that it accounts for the total amount of non-functional tissue. In addition, there is evidence for the presence of necrotic cardiomyocytes in HF. Therefore, the objective of this study was to investigate the necroptotic proteins regulating necroptosis, a form of programmed necrosis, and thereby assess its potential role in human end-stage HF. Methods Left ventricular samples of healthy controls (C) and patients with end-stage HF due to myocardial infarction (CAD) or dilated cardiomyopathy (DCM) were studied. Immunoblotting for necroptotic and apoptotic markers was performed. Triton X-114 fractionated samples were analyzed to study differences in subcellular localization. Results Elevated expression of RIP1 (receptor-interacting protein), pSer227-RIP3 and its total levels were observed in HF groups compared to controls. On the other hand, caspase-8 expression, a proapoptotic protease negatively regulating necroptosis, was downregulated suggesting activation of necroptosis signaling. Total mixed-lineage kinase domain-like protein (MLKL) expression did not differ among the groups; however, active cytotoxic forms of MLKL were present in all HF samples while they were expressed at almost undetectable levels in controls. Interestingly, pThr357-MLKL unlike pSer358-MLKL, was higher in DCM than CAD. In HF, the subcellular localization of both RIP3 and pThr357-MLKL was consistent with activation of necroptosis signaling. Expression of main apoptotic markers has not indicated importance of apoptosis. Conclusions This is the first evidence showing that human HF of CAD or DCM etiology is positive for markers of necroptosis which may be involved in the development of HF.